2011
DOI: 10.4081/pr.2012.e1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen treatment of superficial soft tissue lesions in children with oncologic disease

Abstract: This study aimed to assess the feasibility and results of hyperbaric oxygen therapy (HOT) as supportive treatment of lesions of superficial soft tissues in children with oncological diseases. This was a retrospective analysis and review of all records of children observed at the Pediatric Hematology-Oncology Department of the University of Padova and treated adjuvantly with HOT. Between 1996 and 2010, 12 patients (5 males and 7 females, median age 7 years, range 0.5–16) underwent HOT. The effectiveness of HOT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…There is no standard of care for the treatment of ON in children with ALL, especially for the early stages; meanwhile HBO showed itself to be safe and effective in most patients even those dose immunocompromised or critical ill (35,36). Our preliminary experience in HBO (3 patients included in the present study and treated until 2014) suggested its implementation in our current treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard of care for the treatment of ON in children with ALL, especially for the early stages; meanwhile HBO showed itself to be safe and effective in most patients even those dose immunocompromised or critical ill (35,36). Our preliminary experience in HBO (3 patients included in the present study and treated until 2014) suggested its implementation in our current treatment approach.…”
Section: Discussionmentioning
confidence: 99%